Adoption determinants of the International Accounting Standards IAS/IFRS by the developing countries - Fatma Zehri; Jamel Chouaibi (Journal of Economics, Finance and Administrative Science, 2013)
This paper's main objective is to identify certain explanatory factors that likely clarify the choice of applying IAS/IFRS adopted by developing countries (DCs) up until the year 2008. Based on a sample consisting of 74 DCs, the empirical results have indicated that the DCs most likely to adopt IAS/IFRS have a high level of economic growth, along with a legal system of common law and an advanced educational level. – – El principal objetivo de este documento es identificar ciertos factores que probablemente esclarezcan la opción de aplicar IAS/IFRS adoptadas por los países en desarrollo hasta el a\~no 2008. Basados en una muestra de 74 países en desarrollo, los resultados empíricos han demostrado que la mayoría de ellos probablemente tienen un alto nivel de crecimiento económico, junto con un sistema jurídico de derecho consuetudinario y un nivel de educación avanzado.
Keywords: G00; G20; 330; Developing countries; International financial reporting standards; Institutional environment; Países en desarrollo; Normas internacionales de información financiera; Ámbito institucional